CONSTRUCTIVE AND TECHNOLOGICAL ASPECTS OF THE IMPLEMENTATION OF THE OPTIC-ACOUSTIC METHOD FOR RESEARCHING THE THERMODYNAMIC PROPERTIES OF AROMATIC COMPOUNDS AND THEIR FLUORINATED ANALOGUES - Burmistrov, Oleksandr; Sukhovirska, Liudmyla; Bolilyi, Vasyl (Physical and Mathematical Education, 2024)
Formulation of the problem. The study of acoustic spectra of aromatic compounds and their fluorinated analogs shows that a simple area of acoustic dispersion is observed in these liquids, which is due to the processes of vibrational relaxation – the transfer of the energy of translational motion of molecules to the vibrational degrees of freedom and vice versa. Differences in the interpretation of molecular mechanisms of acoustic relaxation are explained by the fact that, until recently, there was no experimental data on the acoustic spectra of aromatic compounds and their fluorinated analogs in wide ranges of temperatures and frequencies.Materials and methods. The study examines the Mandelstam-Brillouin method of acoustic spectroscopy, improved by an automated experimental setup.To achieve the goal, the following research methods were used: empirical (observation, comparison), theoretical (material analysis, idealization, imaginary experiment), and computer modeling.Results. Modern advances in Mandelstam-Brillouin spectroscopy make it possible to reliably measure the velocity and absorption of hypersonic waves in transparent liquids at different temperatures (including even the critical ones), as well as to study the Rayleigh scattering spectra in liquid crystals, metals, and semiconductors. The improved experimental setup made it possible to measure the absorption and speed of sound in a wider temperature range and frequency range (up to 7.0 GHz) in a number of aromatic compounds and their fluorinated analogs, to clarify the molecular mechanisms responsible for acoustic relaxation.Conclusions. This work investigates an approach to explaining the molecular mechanisms of relaxation processes in liquid aromatic compounds and their fluorinated analogs, which is based on taking into account the role of weak intermolecular bonds.
Keywords: acoustic spectrum; aromatic compound; Mandelstam-Brillouin spectroscopy; optical installation; experiment